On the Importance of the Philosophy of Well-being - Kwarciński, Tomasz (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2019)
Objective: A weak approach to well-being policy means that government’s goal should be to choose policies that make people better off over those that make them worse off, with other things being equal. The question is what kind of underlying assumptions should be fulfilled to achieve this goal. In particular, do policymakers have to agree on some substantive theory of well-being, like hedonism or objective list theory, or persist in choosing the formal preference satisfaction theory of well-being? According to Haybron and Tiberius (Well-being Policy: What Standard of Well-being?, “Journal of the American Philosophical Association” 2015, vol. 1, no 4), we can avoid raising such questions by drawing a strict distinction between the varieties of concepts or theories of well-being and policy processes aiming at promoting the well-being of citizens. They claim that such policies are “justified only when they are grounded in the conceptions of the well-being of those on whose behalf policy is being made”, and call this approach “pragmatic subjectivism” (p. 713). From their reasoning it follows that policymakers need not develop the appropriate concept of well-being, but can leave it to citizens to choose. The paper examines Haybron and Tiberius’ proposal and defends the claim that while theoretically we can avoid discussing the concept of well-being when we follow pragmatic subjectivism, we cannot do this in practice. Research Design & Methods: The paper uses an argument analysis. Findings: One way or another we will have to move in the direction of purely formalistic preference satisfaction theory or some substantive approaches like hedonism or objectivism. If we do not want to take for granted the incoherent intuitive concepts of well-being people hold, and because “well-being” is a normative concept, we have to develop philosophical theories of well-being that openly reveal their strengths and weaknesses. Implications / Recommendations: To facilitate the process of political decision-making, philosophically informed measures of well-being are needed. To a certain extent, those measures already exist, and they are widely applied by policymakers, e.g., GDP per capita, the Human Development Index or various happiness / subjective well-being indices. However, they seem to be either insufficient or purely philosophically informed. Contribution: The paper contributes to the development of the analysis of well-being and measures its philosophical underpinnings.